Identifikasi Bakteri Salmonella sp pada Bakso Ayam yang Dijual di Pasar Tradisional Kecamatan Denpasar Selatan - Dominika Siahaan, Graciella Tio; Sugitha, I Made; Indri Hapsari Arihantana, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 2 (2024): Jurnal ITEPA, 2024)
Indonesia is a country that is rich in various kinds of food products, one of which is meatballs. Meatballs are food products made from crushed meat, mixed with flour and some complementary spices, formed into rounds, and boiled. Meatballs can be found in almost all cities in Indonesia because this product is much- loved by the community, one of which can be found in traditional markets in the South Denpasar district. The market is very vulnerable and has quite a high risk of pathogenic microbial contamination. Improper processing of meatballs and low sanitation of the environment where they sell and personal hygiene of traders can increase bacterial contamination. This study aims to determine the contamination of Salmonella sp bacteria in chicken meatballs and the application of sanitation and hygiene to chicken meatballs sold in traditional markets in the South Denpasar district. This study used survey methods and sampling techniques with saturated sampling methods. The total samples used in this study were 10 samples which were tested with SSA media, gram staining, and TSIA test. The data obtained were presented in the form of tables and pictures and analyzed descriptively. The results showed that 7 samples of chicken meatballs sold in traditional markets in the South Denpasar District contained Salmonella sp. These results indicate that chicken meatballs sold at traditional markets in South Denpasar District have not met the requirements of the Food and Drug Supervisory Agency Regulation No. 13 of 2019 concerning the maximum limit of microbial contamination in processed food, Salmonella sp. in meatballs is negative/25g and some traders have not implemented good hygiene and sanitation practices.